Survey of otitis externa in American Cocker Spaniels in Finland - Kaimio, Mirja (Acta Vet Scand, 2017)
BACKGROUND: American Cocker Spaniels are overrepresented among breeds that require surgery as a treatment of end-stage otitis externa. However, the prevalence of otitis externa (OE) in this breed remains unknown. We reviewed the year 2010 medical records of 55 private veterinary clinics in Finland to determine the prevalence of OE in American Cocker Spaniels compared with English Cocker and English and Welsh Springer Spaniels. An American Cocker Spaniel owner questionnaire was designed to identify potential risk factors for end-stage OE. RESULTS: From the medical records of 98,736 dogs, the prevalence of OE was highest in Welsh Springer Spaniels (149 out of 468, 31.8%, [95% confidence interval 27.6–36.0]), followed by American Cocker (89/329, 27.0%, [22.2–31.7]), English Springer (96/491, 19.6%, [16.1–23.1]) and English Cocker Spaniels (231/1467, 15.7%, [13.8–17.6]). The mean number of OE episodes in ear-diseased dogs and the number of ear surgeries were highest in American Cocker Spaniels. Owner questionnaires were received for 151 American Cocker Spaniels, 85 (56%) of which had suffered from OE. In 47% (40/85) of these dogs, OE occurred without concurrent skin lesions, 46% (33/72) displayed the first signs of OE before 1 year of age. In 24% (20/85) of the dogs, the signs of OE recurred within 1 month or continued despite treatment, 16% (14/85) required surgery (n = 11) or were euthanized (n = 5; 2 of the operated dogs and 3 others) due to severe OE. The onset of OE before the age of 1 year significantly increased the risk (OR 3.8, 95% CI 1.1–13.6) of end-stage OE. CONCLUSIONS: The prevalence of OE in American Cocker Spaniels in Finland was higher than previously reported in Cocker Spaniels, but the highest prevalence of OE was found in Welsh Springer Spaniels. Compared to the other Spaniels, OE was more often recurrent and more frequently surgically managed in American Cocker Spaniels. Based on the questionnaire, early onset (<1 year) of OE increased the risk of end-stage OE. In American Cocker Spaniels, OE requires an intensive approach from the first treatment, and prevention of recurrence should be emphasised. The causes and treatment of OE in this breed warrant further study.